The pervasive nature of unconscious social information processing in executive control - Prabhakaran, Ranjani; Gray, Jeremy R. (Frontiers in Human Neuroscience, 2012)
Humans not only have impressive executive abilities, but we are also fundamentally social creatures. In the cognitive neuroscience literature, it has long been assumed that executive control mechanisms, which play a critical role in guiding goal-directed behavior, operate on consciously processed information. Although more recent evidence suggests that unconsciously processed information can also influence executive control, most of this literature has focused on visual masked priming paradigms. However, the social psychological literature has demonstrated that unconscious influences are pervasive, and social information can unintentionally influence a wide variety of behaviors, including some that are likely to require executive abilities. For example, social information can unconsciously influence attention processes, such that simply instructing participants to describe a previous situation in which they had power over someone or someone else had power over them has been shown to unconsciously influence their attentional focus abilities, a key aspect of executive control. In the current review, we consider behavioral and neural findings from a variety of paradigms, including priming of goals and social hierarchical roles, as well as interpersonal interactions, in order to highlight the pervasive nature of social influences on executive control. These findings suggest that social information can play a critical role in executive control, and that this influence often occurs in an unconscious fashion. We conclude by suggesting further avenues of research for investigation of the interplay between social factors and executive control.